Development of Android-Based Go Swim Education Learning Media on Material Basic Swimming Techniques for Junior High School Students (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
This study aims to examine and analyze the learning of media models and the development of the Android-based Go Swim Education application on Material Basic Swimming Techniques for Junior High School Students. The research method used was the research and development of Sugiyono's research steps which are adapted into 10 steps. The results showed that development of the Android-Based Go Swim Education application was good and practicable to be a learning media of junior high school students who are made it easier for teachers and students to achieve goals of basic swimming technique material as learning object. Good and practicable results were obtained from the validation results of learning media experts of 93.75% which means very practicable, and the validation of physical education experts which shows an assessment result of 87% which means very good. After being trial by learning media experts and physical education experts, it was then trialed with physical education SMP teachers. The first physical education teacher trial getting scored 93% in the very good category, then the second teacher trialed getting scored 90% in the very good category. Trial on this application was carried out in two stages, was small-group and large-group trials. In a small group trial, this application received an assessment result of 91.25% which in the very decent category. In the large group trial, this application received an assessment result of 88.66% which was in the very decent category. Therefore, it can be concluded that the Go Swim Education application was one of developments of the technology-based physical education learning media to make it easier for teachers and students to achieve learning goals, than the menu in the Go Swim Education application has benefits both practically and theoretically to help sports and health physical education teachers utilize materials with basic swimming techniques in junior high schools.